Immediate Transurethral Plasma Kinetic Enucleation of the Prostate Gland for Treatment of Benign Prostatic Hyperplasia-Associated Massive Hemorrhage: A Single-Center Experience - Gan, Yu; Deng, Liang; He, Qiangrong; Li, Chao; He, Leye; Long, Zhi (Frontiers in Surgery, 2022)
Purpose: Benign prostatic hyperplasia (BPH)-associated massive hemorrhage (BMH) is a urological emergency. We evaluated the outcome from immediate transurethral plasma kinetic enucleation of the prostate gland (i-TUPKEP) for BHM treatment. Methods: We retrospectively analyzed the records of 49 patients with acute BMH who underwent i-TUPKEP between January 2014 and November 2018 at our institution. The hemostatic effect, International Prostate Symptom Score (IPSS) and quality of life (QoL) score were evaluated preoperatively as well as 3, 6, and 12 months postoperatively. Postoperative follow-up also included measurement of the peak flow rate (Qmax) and post-void residual urine volume (PVR). Clinical characteristics, weight of resected tissue, duration of bladder irrigation, duration of hospital stay, complications, as well as the time required for enucleation and resection, were recorded. Results: BMH causes were attributed to transurethral surgery (17/49, 34.7%), violent catheterization (13/49, 26.5%), cystoscopy (10/49, 20.4%), and urethral dilatation (9/49, 18.4%). Bleeding was from different sites of prostate-gland tissues during i-TURKEP. i-TUPKEP controlled BMH effectively and induced immediate, notable, and lasting improvements in the IPSS and QoL score. Qmax was close to normal, and the PVR was within the physiological range, postoperatively. Long-term complications were not observed. Conclusion: Our preliminary data suggest that i-TUPKEP is a feasible method for controlling BHM and relieving BPH symptoms.